Conceptual design of a self-propelled mechanized pineapple transplanter - Saharrudin, Ahmad Safiuddin; Mahadi, Muhammad Razif; Mohd Kassim, Muhammad Saufi; Wan Hasan, Wan Zuha (HH Publisher, 2024)
Pineapple cultivation involves several operations, and planting is considered one of the critical operations. The existing machine cannot be applied because it will damage the plastic mulch. This study aims to present a design concept for the development of a pneumatic-powered pineapple transplanter. The major components will be the planting mechanism and the sucker feed mechanism that will be integrated into a semi-autonomous sucker planting mechanism by soil opener, which consists of a puncher and digger to allow the sucker to enter into the grow bed and then compact with soil. The puncher and digger are powered by pneumatic means. The pineapple transplanter was designed with a width of 1074mm and a clearance of 320mm, which could maneuver over the soil bed. From the CAD simulation, it takes 57mm of extending actuator to open the digger 45 degrees. Air compressors provide 8 bars of pressure to punch a hole in the soil with 5 bars of pressure. The design can continue with fabrication and can be used for future research.